Protective effects of spironolactone against anthracycline‐induced cardiomyopathy. (20th November 2014) - Akpek, Mahmut; Ozdogru, Ibrahim; Sahin, Omer; Inanc, Mevlude; Dogan, Ali; Yazici, Cevat; Berk, Veli; Karaca, Halit; Kalay, Nihat; Oguzhan, Abdurrahman; Ergin, Ali
<x xml:space="preserve">Abstract</x> Aims The protective effect of beta‐blockers, ACE inhibitors, and ARBs on anthracycline cardiotoxicity has already been demonstrated, but the effect of aldosterone antagonism, which inhibits the last step of the renin–angiotensin–aldosterone system (RAAS), was questioned. This study sought to investigate whether spironolactone protects the heart against anthracycline‐induced cardiotoxicity. Methods and results Eighty‐three female patients who were diagnosed with breast cancer were included in the study. The study population was randomized into spironolactone and control groups. A dose of 25 mg/day spironolactone was administered to the patients in the spironolactone group. There were 43 patients (mean age 50 ± 11 years) in the spironolactone group and 40 patients (mean age 51 ± 10 years) in the control group. LVEF decreased from 67.0 ± 6.1 to 65.7 ± 7.4 (P = 0.094) in the spironolactone group, and from 67.7 ± 6.3 to 53.6 ± 6.8 in the control group (P < 0.001). When the general linear model was applied, the interaction of LVEF decrease between groups was significantly lower in the spironolactone group than in the control group (P < 0.001). The diastolic functional grade of subjects in the spironolactone group was protected (P = 0.096), whereas it deteriorated in the control group (P < 0.001). Conclusion We showed that spironolactone administration used simultaneously with anthracycline group chemotherapeutics protects both myocardial systolic and diastolic functions. Spironolactone can be used to protect against anthracycline‐induced cardiotoxicity. Trial registration: NCT02053974.